Spatial Analysis of Flash Flood Susceptibility in Ulu Ogan District - Salma Aulia Az-zahra; Budhi Setiawan; Yogie Zulkurnia Rochmana (Universitas Negeri Gorontalo, 2026)
Ulu Ogan District, Ogan Komering Ulu Regency, is an area with a history of flash flood events triggered by high rainfall intensity and steep topographic conditions. This study aims to analyze flash flood susceptibility using the Analytical Hierarchy Process (AHP) to determine parameter weights and a Geographic Information System (GIS)-based Weighted Overlay technique to produce a susceptibility zoning map. The parameters used include rainfall, slope, river distance, soil type, land use, and elevation. Rainfall data were obtained from CHIRPS, while the Digital Elevation Model (DEM) was derived from DEMNAS with a spatial resolution of 30 m. Land use data were obtained from the Ina-Geoportal (RBI dataset) provided by the Indonesian Geospatial Information Agency (BIG). All spatial datasets were processed in ArcGIS and resampled to a uniform spatial resolution to ensure consistency in the overlay analysis. The results indicate that areas classified as high susceptibility cover 1.35 km² (0.52%) and are concentrated along the Ogan River, particularly in low-lying areas located very close to the river channel. Moderate susceptibility areas cover 54.38 km² (21.10%) and generally follow the pattern of valleys and river networks. Meanwhile, low susceptibility areas dominate the study area, covering 201.99 km² (78.37%), and are mostly located in higher topographic regions farther from the main river channel. Despite the dominance of low susceptibility areas, river valley zones remain vulnerable to flash floods due to the localized and rapid nature of flash flood events.